Drosophila melanogaster como organismo modelo para triagem de compostos reativadores de acetilcolinesterase - Macedo , Pablo Echeverria (2021)
Among the most used agrochemicals to supply the increased demand for application that can provide security to the demand for domestic agricultural production is the organophosphate compound classified as an insecticide, chlorpyrifos. Acute poisonings caused by this compound lead to inhibition of the enzyme acetylcholinesterase, an event that causes the accumulation of the neurotransmitter acetylcholine in the synaptic cleft, as well as not the consequent development of a condition called a cholinergic syndrome. Treatment aimed at cases of intoxication by this compound is based on the administration of enzyme reactivators, structures such as oximes. Therefore, the development of this work consisted of evaluating, through in silico, in vitro, and in vivo approaches, the use of the model organism Drosophila melanogaster as a platform for screening the reactivators of the enzyme acetylcholinesterase, pralidoxime, trimedoxime, obidoxime, HI-6, melanogaster, K027, and K048 against inhibition induced by the organophosphate chlorpyrifos. The in silico approach follows through molecular anchoring that chlorpyrifos has access to the Gorge site of the acetylcholinesterase enzyme from D. melanogaster, as well as the interaction energies and possible conformations adopted by the oximes evaluated in this region. The in vitro approach changed that the oximes pralidoxime and K048 had higher reactivation rates of the enzyme acetylcholinesterase from D. melanogaster, 38.1%, and 38.7%, respectively, followed by the oximes trimedoxime with 28.3%, K027 with 17.6%, obidoxime with 17%, methoxime with 15.3% and HI-6 with 15.2%. The oximes evaluated demonstrated a discrete capacity of antioxidant action by the ABTS and DPPH methods, not surpassing ascorbic acid. No correlation was found between the reactivation potential of acetylcholinesterase by oximes and their antioxidant activities. The in vivo approach includes D. melanogaster specimens exposed to chlorpyrifos and treated with pralidoxime and K048 oximes, protection concerning activity rate, locomotor activity, and acetylcholinesterase enzyme activity. Therefore, we demonstrate the potential use of D. melanogaster for prior screening of acetylcholinesterase reactivating compounds, which may be an important tool for the discovery of new oximes.